Wheelchair mobility performance only supports the use of two classes in wheelchair basketball - van der Slikke, R.; Berger, M.; Bregman, D. (ISBS Proceedings Archive (Michigan), 2017)
The purpose of this study was to determine the effect of functional classification on wheelchair mobility performance in wheelchair basketball, measured during match play (n=29) and a standardised field test (n=47). In unconstrained field test conditions, wheelchair mobility performance outcomes only differed significantly between the low classified players compared to the adjacent higher class athletes. In match play differences between adjacent classes are less prominent, with a more even rise in performance with increase in classification. These differences in patterns were expected to be the consequence of match related factors, field position in particular. Differentiated wheelchair mobility performance measurement on and off court could corroborate classification guidelines or provide bases for a reduced number of classes.